SOME ASPECTS REGARDING COMPUTER AIDED DESIGN OF CAM MECHANISMS WITH FLAT FACE OSCILLATING FOLLOWER - Stelian ALACI; Florina Carmen CIORNEI; Dumitru AMARANDEI; Constantin FILOTE; Simion PĂTRAŞ-CICEU; Dorel PRODAN (Fiabilitate şi Durabilitate)
The paper presents some aspects concerning the design of cam mechanisms with oscillating flat facedfollower, using computer softwares. There are deduced the analytical equations for the profile of the cam, thusenabling the study of mechanism’s reliability. There are emphasised the effects due to an inadequate choice oflaw of motion, mainly shocks during mechanism operation.